Using growth curves model to analyse the prospects of China–Pakistan oil and LNG transportation corridor - Huang, Wencheng; Shuai, Bin; Shen, Yong (Transport, 2022)
In order to analysing the oil and Liquefied Natural Gas (LNG) import and consumption changing trends, the Occurrence Period (OP), Growth Period (GP) and Maturation Period (MP) of oil and LNG import and consumption in China, and studying how the oil and LNG import and consumption changing trends influence the development of China–Pakistan oil and LNG transportation corridor (CPOLTC), in this paper we apply a Growth Curve Model (GCM) based approach to solve the problems mentioned above. First, the Chinese oil and LNG import and consumption changing trends are analysed by applying the GCM. The results show that oil and LNG consumption and import belong to the GP because of the fast industrialization and urbanization development, so the oil and LNG import and consumption demand will increase fast; Then, the External Dependence (ED) is applied to describe the oil and LNG consumption dependence degree in China, the results show that import will remain high ED value, especially for the oil import (over 70%), which means the security of the energy supply chain still remains the central idea of Chin’s energy policies. Finally, the challenges and key issues of CPOLTC is analysed. Challenges are: domestic political struggles and institutional defects in Pakistan make the CPOLTC projects lacking of implementation, security along the corridor, influence and competition from external forces, impacts of western project culture, the comprehensive projects establishment ability in Pakistan, etc. The key issues are: Value Engineering (VE) researches for projects, Chinese element such as project construction, management, standards and specifications, assessment of the projects’ life cycle and so on.